Dalitz plot analysis of the D+→K−K+K+ decay - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kecke, Matthieu; et al. (Journal of high energy physics, 2019)
The resonant structure of the doubly Cabibbo-suppressed decay D+→K−K+K+ is studied for the first time. The measurement is based on a sample of pp-collision data, collected at a centre-of-mass energy of 8 TeV with the LHCb detector and corresponding to an integrated luminosity of 2 fb−1. The amplitude analysis of this decay is performed with the isobar model and a phenomenological model based on an effective chiral Lagrangian. In both models the S-wave component in the K−K+ system is dominant, with a small contribution of the ϕ(1020) meson and a negligible contribution from tensor resonances. The K+K− scattering amplitudes for the considered combinations of spin (0,1) and isospin (0,1) of the two-body system are obtained from the Dalitz plot fit with the phenomenological decay amplitude. Open image in new window
Gesehen am 09.05.2019
LHCb Collaboration: R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, A. Piucci, M. Stahl, S. Stemmle, N. Skidmore, U. Uwer, A. Zhelezov [und weitere] (LHCb collaboration)
Im Titel sind "+" und "-" hochgestellt